2018
DOI: 10.3390/app8071053
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinearity Analysis and Multi-Model Modeling of an MEA-Based Post-Combustion CO2 Capture Process for Advanced Control Design

Abstract: Abstract:The monoethanolamine (MEA)-based post-combustion CO 2 capture plant must operate flexibly under the variation of the power plant load and the desired CO 2 capture rate. However, in the presence of process nonlinearity, conventional linear control strategy cannot achieve the best performance under a wide operation range. Considering this problem, this paper systematically studies the multi-model modeling of the MEA-based CO 2 capture process for the purpose of (1) implementing well-developed linear con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Assessing the possibilities of COSMO-RS for the important parameters of prediction and analysis, the current study is proposed for CO 2 capture through absorption. The nonlinearity exhibited in the absorption of CO 2 in previously studied solvents , suggests that using a quantum calculation method may yield an accurate estimation of various involved thermodynamic properties. The selection of proposed blends is based on an extensive literature survey.…”
Section: Introductionmentioning
confidence: 99%
“…Assessing the possibilities of COSMO-RS for the important parameters of prediction and analysis, the current study is proposed for CO 2 capture through absorption. The nonlinearity exhibited in the absorption of CO 2 in previously studied solvents , suggests that using a quantum calculation method may yield an accurate estimation of various involved thermodynamic properties. The selection of proposed blends is based on an extensive literature survey.…”
Section: Introductionmentioning
confidence: 99%
“…The fuzzy modelling technique was also used in Liang et al [93], where local state-space models were identified from data and then linked together according to the CO2 capture level. The developed fuzzy model was used to capture the dynamics among CO2 capture level, re-boiler temperature, lean solvent and re-boiler steam flow rates.…”
Section: Dynamic Identification Of the Solvent Based Pccmentioning
confidence: 99%
“…Optimizing control architectures by comparing PID (proportional-integral-derivative) and MPC were also studied by Arce et al [35]. Liang et al [36] propose a multi-linear model for MEA-based CO 2 capture. The proposed approach first identifies local linear models at typical operating points.…”
Section: Introductionmentioning
confidence: 99%